2011
DOI: 10.1038/gt.2010.165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of systemic targeting of RET oncogene-based MTC with tumor-selective peptide-tagged Ad vectors in clinical mouse models

Abstract: Significant advantage of targeted antitumoral treatment consists in the possibility to restrict maximum therapeutic efficacy to the malignant cell population by reducing toxicity in healthy tissues. Using different clinical models for aggressive medullary thyroid carcinoma (MTC), we have recently identified peptide ligands that bind highly selective to tumor cells. By linking the most convincing SRESPHP peptide to an adenoviral (Ad) vector expressing the MTC-related oncogene inhibitor RETDTK, gene transfer was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The last step of Ad entry into target cells depends on the interaction between RGD motif at the penton base protein and the host cell integrins [100]. Ad vectors containing this RGD peptide in the HI loop of the fiber showed higher yields of gene transfer than vectors containing the identical peptide attached at the fiber‘s C-terminus, due to the easy access to the receptor [39,101,102]. Many groups transduced effectively different types of tumor cells by inserting this RGD motif into the HI loop of the Ad fiber in vitro [103] and in vivo [104,105].…”
Section: Methods To Alter the Natural Ad Vector Tropismmentioning
confidence: 99%
See 2 more Smart Citations
“…The last step of Ad entry into target cells depends on the interaction between RGD motif at the penton base protein and the host cell integrins [100]. Ad vectors containing this RGD peptide in the HI loop of the fiber showed higher yields of gene transfer than vectors containing the identical peptide attached at the fiber‘s C-terminus, due to the easy access to the receptor [39,101,102]. Many groups transduced effectively different types of tumor cells by inserting this RGD motif into the HI loop of the Ad fiber in vitro [103] and in vivo [104,105].…”
Section: Methods To Alter the Natural Ad Vector Tropismmentioning
confidence: 99%
“…The ligand, which also binds efficiently to human MTC cells was covalently linked to the Ad capsid that carried a RET inhibitor as therapeutic gene. Systemic delivery of this peptide-tagged Ad vector led to the substantial growth reduction of orthotopic and disseminated xenograft tumors, while the interaction with other organs, such as the liver, was largely abolished [39]. This precedent opens a road towards using peptide-mediated adenoviral gene transfer to achieve an efficient and selective antitumoral response, even at the stage of metastatic disease.…”
Section: Screening For Cell-specific Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, adenovirus tends to be removed by the immune system, due to pre-existing antibodies [14]. Better adenoviruses for in- vivo use are being generated, by modifying tropism and immuno-susceptibility [3], [7], [10], [11], [17], [18]. Recently, it was reported that chemical coupling of adenovirus with a peptide that has a high affinity for a hepatic stellate cell (HSC) surface protein drastically facilitates infection of the corresponding cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Injection of an Ad vector expressing dominant-negative RET protein into MTC of the thyroid glands significantly decreased the tumor size after two weeks (Drosten et al, 2004). To enhance tumor specificity of anti-RET Ad vectors in order to target systemically spreaded medullary thyroid carcinoma cells, we have recently identified a number of MTCspecific peptides that can be used to efficiently redirect the therapeutic gene to primary MTC, their migrating populations, and potentially tumor metastases under in vivo conditions (Böckmann et al, 2005a;Böckmann et al, 2005b;Schmidt et al, 2011).…”
Section: Medullary Thyroid Carcinoma -Standard Diagnosis and Treatmentmentioning
confidence: 99%